Behavior of Farmers in Using Pesticides for Vegetable Farmers in Muang District, Khon Kaen Province - Nathapindhu, Somchai; Nathapindhu, Ganjana; Nippanon, Charuwan; Chanpong, Bussaba (Journal of Health Science of Thailand, 1994)
The objectives of this research were to study the behavior of vegetable farmers in using pesticides. the kinds of pesticides used, and also the knowledge and attitude of the vegetable farmers in using the pesticides. The study was conducted in the period between January - June 1992. by interviewing 170 vegetable farmers from 170 farms from 5 villages in Muang District, Khon Kaen Province. Also the research was qualitatively conducted by indepth interview and observation. It was found that most of vegetable farmers used pesticides in the afternoon during 4.00-6.00 PM, and 22.94% of the farmers used pesticides both in the morning (6.00—8.00 AM.) and atternoon. A small number of farmers took intermission to drink water even without prewashing their hands by soaps or detergents. Most of vegetable farmers used bath towels to cover their noses and mouths to protect pesticide hazard. They also used clothes to cover their hair, and poor quality mask for respiratory protection. 10.59% of farmers dressed the mselves in complete safety suits (by wearing gloves, boots and masks) to avoid the pesticide hazards. 94.12% of them took a bath after ﬁnish spraying the pesticides. 60% of farmers developed abnormal symptoms from pesticide use. These included sweat at arms and legs, itched at hands and skin, benumbed at the parts of body that touched the pesticides, vertigo, nausea, vomit, 25.49% of the farmers who got those abnormal symptoms would have abnormal symptoms on their bodies all the times when they used the pesticides in the farms. The pesticides they used in vegetable farms were Mevinphos, Methyl Parathion, Methamidophos and Prothiophos. Ratio of pesticides to water as the pesticide concentration they used, they studied from the lebels on pesticide containers, they mixed some violent chemical substances in the pesticides in order to increase more effectiveness, most of vegetables that the farmers spread the pesticides on were puk-kana, white lettuces and long beans, 96.47% of farmers said that the pesticides they used in the farms were very hazardous to their bodies, to avoid the hazards from using those pesticides they would perform the mselves follow the recommendations of the lebel: 0n pesticide containers for examples; dressing in the complete safety suits, drinking the beverage (Orange Juice) after spraying the pesticides in the farme.